Rare bird sighting for Peregrine Falcon at Council Bluffs in 1986 - Toll, Jerryet al (1986)
Rare bird sighting for a Peregrine Falcon at Council Bluffs in Pottawattamie County, IA on April 4, 1986. Epson - sheet feed